Symptoms of fusarium graminearum infection in irrigated rice grains Sintomas de infecção por Fusarium graminearum em grãos de arroz irrigado - Scheidt B.T.* (2019)
© 2019, Universidade Federal de Santa Maria. All Rights Reserved.The fungus Fusarium graminearum was one of the first pathogens described as causing infections in rice; however, in Brazil, there is no description of its occurrence in panicles. The present study aimed to describe the symptoms caused by F. graminearum infection in irrigated rice grains. The experiment was conducted in a greenhouse in duplicate using the irrigated rice cultivar SCS 121CL and hybrid INOV CL at the R4 (flowering) stage. Two isolate of Fusarium graminearium species complex 15A (F. graminearium - 15-ADON) and FmNiv (F. meridionale - Nivalenol), was inoculated onto panicles by spraying with macroconidia and the development of symptoms was monitored until harvest. There was no difference in symptoms among isolates. Light brown spots were observed in the glumes three days after inoculation. These later evolved into brown lesions of irregular shape and size. The glume darkened to purple when the grains were in the filling stage (R6). On maturation, the glume showed dark brown coloration. Severely infected grains were shriveled and brittle.